Orofacial overgrowth with peripheral nerve enlargement and perineuriomatous pseudo-onion bulb proliferations is part of the PIK3CA-related overgrowth spectrum - Koutlas, Ioannis G.; Anbinder, Ana-Lia [UNESP]; Alshagroud, Rana; Rodrigues Cavalcante, Ana Sueli [UNESP]; Al Kindi, Mohammed; Crenshaw, Molly M.; Sapp, Julie C.; Kondolf, Hannah; Lindhurst, Marjorie J.; Dudley, Jeffrey N.; Johnston, Jennifer J.; Ryan, Elyse; et al. (Elsevier, 2020)
Individuals with orofacial asymmetry due to mucosal overgrowths, ipsilateral bone and dental aberrations with perineurial hyperplasia and/or perineuriomatous pseudo-onion bulb proliferations, comprise a recognizable clinical entity. In this article, we describe three individuals with this clinical entity and mosaic PIK3CA variants c.3140A>G (p. His1047Arg), c.328_330delGAA (p. Glu110del), and c.1353_1364del (p.Glu453_Leu456del). We conclude that the identification of these mosaic variants in individuals with orofacial asymmetry presenting histopathologically perineurial hyperplasia and/or intraneural pseudo-onion bulb perineurial cell proliferations supports the inclusion of this clinical entity in the PIK3CA-related overgrowth spectrum.
Keywords: face; oral mucosa; overgrowth; perineurium; peripheral nerve; PIK3CA; pseudo-onion bulbs